2005
DOI: 10.1158/1055-9965.epi-05-0089
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features of Adult Glioma Associated with Patient Race/Ethnicity, Age, and a Polymorphism inO6-Methylguanine-DNA-Methyltransferase

Abstract: Background: Risk factors for adult glioma in the San Francisco Bay Area include well-known demographic features such as age and race/ethnicity, and our previous studies indicated that these characteristics are associated with the TP53 mutation status of patients' tumors. We enlarged our study to assess the relationships of risk factors with TP53 as well as epidermal growth factor receptor (EGFR) and murine double minute-2 (MDM2) gene amplification and expression and the germ line Leu84Phe polymorphism in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 54 publications
2
51
0
1
Order By: Relevance
“…However, at present, these are not clearly established. There are a substantial number of epidemiological and biochemical reports on the properties of these variants (reviewed in [48]) but these do not provide a consistent picture with some studies showing increased risk of tumor development and others not [19,20,22,23,25,26,29,31,[45][46][47]. This may be a consequence of the small sample size in most of these studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, at present, these are not clearly established. There are a substantial number of epidemiological and biochemical reports on the properties of these variants (reviewed in [48]) but these do not provide a consistent picture with some studies showing increased risk of tumor development and others not [19,20,22,23,25,26,29,31,[45][46][47]. This may be a consequence of the small sample size in most of these studies.…”
Section: Discussionmentioning
confidence: 98%
“…Variants W65C [15,16], L84F [15][16][17][18][19][20][21][22][23][24][25][26][27][28], I143V/ K178R [17][18][19][20][21][22][23][24]27,[29][30][31] and G160R [29,32] have been reported by multiple laboratories. These reports raise the possibility that there may be individual variation in response to hAGT inactivators.…”
Section: Introductionmentioning
confidence: 99%
“…Studying genetic variants in this panoply of DNA repair genes might contribute to a better understanding of gliomagenesis, progression, and response to therapy (mostly DNA targeting agents). Some of the most intriguing and consistent findings of the past decade of neuro-oncology research are the statistically significant inverse associations between risk of gliomas in adults and histories of allergies and/or chickenpox, IgG antibodies to varicella-zoster virus, and levels of serum IgE (Wiemels et al, 2004;Wrensch et al, 2001;2005). A later study used germline polymorphisms in genes associated with asthma and allergies (IL-4RA, IL-13 and ADAM33) as biomarkers for the presence of these conditions, as genetic polymorphisms could not be influenced by the presence of glioma.…”
Section: Genetic Polymorphismsmentioning
confidence: 91%
“…Studies using elegant mouse models have recently shown that the specific inactivation of PTEN in the mouse brain caused its overgrowth and abnormal proliferation of astrocytes (Fraser et al, 2004). Also in mouse studies, inactivation of PTEN has been associated with increased angiogenesis, closely paralleling the progression from low-grade to high-grade astrocytomas in humans, which coincides with PTEN loss (Andrew Xiao et al, 2002;2005). Aberrant PI3K signaling commonly results in activation of Akt via phosphorylation of two key residues, T308 and S473, by PDK1 and the mammalian target of rapamycin (mTOR), respectively (Mora et al, 2004;Sarbassov et al, 2005).…”
Section: The Pi3k-akt Pathwaymentioning
confidence: 99%
See 1 more Smart Citation